INDUSTRY 4.0: UZBEKISTAN’S PATH TO DIGITAL TRANSFORMATION (Marketing Journal, 2024)
This article gives the concept of Industry 4.0, studies the experience of foreign leading countries in introducing modern digital technologies into the economy and industry, and evaluates their successes and problems along this path. The successes and problems of various sectors of the economy of Uzbekistan on the path of digital transformation, which lays the foundation for a modern and technological economy , i.e. on the path to transition to Industry 4.0.